Answer:
The average rate of change is
![=-4](https://img.qammunity.org/2020/formulas/mathematics/college/ds29q2i74oz2aj8etebaiejywbzvcxtdso.png)
Explanation:
The average rate of change from x=a to x=b of f(x) is given by;
![=(f(b)-f(a))/(b-a)](https://img.qammunity.org/2020/formulas/mathematics/college/9szedxiubyn841bt6jaz01tgpsyuip09cj.png)
We want to find the average rate of change of the function represented in the table from x=-2 to x=2.
![=(f(2)-f(-2))/(2--2)](https://img.qammunity.org/2020/formulas/mathematics/college/3oca9js8mfrskiyaqjabqkqprfbpbaf0g1.png)
From the table f(-2)=25 and f(2)=9
The average rate of change from x=-2 to x=2 is
![=(9-25)/(2--2)](https://img.qammunity.org/2020/formulas/mathematics/college/un44z3iaan29abjys95nvo79wyvzu9ljdt.png)
![=(-16)/(4)](https://img.qammunity.org/2020/formulas/mathematics/college/snc1dbdfozw2m54hhenzcbhybmdgacfy32.png)
![=-4](https://img.qammunity.org/2020/formulas/mathematics/college/ds29q2i74oz2aj8etebaiejywbzvcxtdso.png)